Hukuman Mati : Dilema Antara Maslahat Mursalah dan Hak Asasi Manusia di Indonesia - Anjas Saputra; Nurul Al-fatihah Rahman; Kurniati Kurniati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research focuses on the dilemma of applying the death penalty in Indonesia, taking into account the aspects of maslahat and justice. The research method used is library research with a normative juridical approach. This research analyzes various legal sources, including Islamic law, to understand different perspectives on the death penalty. In the context of Islamic law, the main sources analyzed include the Al-Qur'an, Hadith, and the views of the scholars. The results show that there is a significant debate between social benefits and justice in the application of the death penalty. On the one hand, the death penalty is considered to have a deterrent effect and maintain public order, while on the other hand, there are concerns about potential judicial error and human rights violations. The conclusion of this study is that the application of the death penalty must be considered very carefully, given the complexity and sensitivity of this issue both from the perspective of positive law and Islamic law.